2012
DOI: 10.1038/nature11163
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 in the Paneth cell niche couples intestinal stem-cell function to calorie intake

Abstract: SUMMARY How adult tissue stem and niche cells respond to the nutritional state of an organism is not well understood. Here, we find that Paneth cells, a key constituent of the mammalian intestinal stem cell (ISC) niche, augment stem cell function in response to calorie restriction (CR). CR acts by reducing mTOR complex 1 (mTORC1) signaling in Paneth cells, and the ISC-enhancing effects of CR can be mimicked by rapamycin. Calorie intake regulates mTORC1 in Paneth cells, but not ISCs, and forced mTORC1 activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
640
4
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 664 publications
(680 citation statements)
references
References 31 publications
30
640
4
6
Order By: Relevance
“…This kind of metabolic interdependence is consistent with the previously elucidated response of Paneth cells and CBCs to caloric restriction [10]. Under conditions of caloric restriction in mice, the intestinal villi shorten and contain fewer differentiated absorptive cells, enterocytes.…”
supporting
confidence: 72%
“…This kind of metabolic interdependence is consistent with the previously elucidated response of Paneth cells and CBCs to caloric restriction [10]. Under conditions of caloric restriction in mice, the intestinal villi shorten and contain fewer differentiated absorptive cells, enterocytes.…”
supporting
confidence: 72%
“…Indeed, recent work has implicated the mTOR pathway in homoestatic control of Lgr5 + stem cell numbers based on nutrient availability (16). PGC-1α is also necessary for intestinal stem cell (ISC) renewal in Drosophila (19), suggesting that the process is conserved across species.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear imperative to understand the regulatory mechanisms governing intestinal stem cell function. Recent work has shown that intestinal stem cells from both flies and humans are sensitive to the metabolic state of the organism and has implicated cellular metabolism as a critical regulatory input of stem cell homeostasis (13)(14)(15)(16). Intestinal stem cells were observed to exhibit higher levels of glycolysis than oxidative phosphorylation compared with their differentiated progeny (17), and the oxidative state of intestinal stem cells impacts the ability of the cells to undergo transformation (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A related possibility is that inhibition of mTORC1 slows aging by increasing autophagy, which helps clear damaged proteins and organelles such as mitochondria, the accumulation of which are also associated with aging and aging-related diseases. Finally, another model suggests that the attenuation of adult stem cells in various tissues plays a central role in organismal aging, and mTOR inhibition boosts the self-renewal capacity of both hematopoietic and intestinal stem cells in mice (Chen et al, 2009;Yilmaz et al, 2012). Ultimately, the importance of mTORC1 signaling in aging likely reflects its unique capacity to regulate such a wide variety of key cellular functions (Fig 5C).…”
Section: Mtor In Agingmentioning
confidence: 99%